Bahasa Bugis: Inflectional Morphology in the Verb - Nurhadi Hamka; Ahmad Rivani Talaohu; La Ode Achmad Suherman (Lembaga Junal dan Publikasi, Universitas Muhammadiyah Buton, 2022)
In this paper, I discuss some morphological processes of inflection in Bahasa Bugis particularly verb, in order to scrutinize some problems that appear in the analysis under a morphemic framework. To have a better understanding towards the analysis of the inflectional case, I will employ an approach of Paradigm Function Morphology by Stump (2001). As a result, inflectional occur depends on the aspect and the person. There are three main aspects found; durative, perfective, and conditional. Of which, durative has four subcategories; durative (repeated), durative (feature & repeated), durative (similar), and durative (repeated & similar). Moreover, perfective aspect is also found to have one subcategory called perfective (past & similar). On the other hand, an interesting phenomenon found in person where the second person differentiated by the pragmatic meaning; more polite and less polite. Finally, through PFM, we can capture the mappings, block by block, show how morphosyntactic features are realized by the exponents in the language.